PENERAPAN PEMBELAJARAN METODE LATIHANUNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VISD NEGERI 007 KAMPUNG BARU KECAMATAN UKUI - Ayi Saepudin (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
Based on the results of tests conducted on students’ social studies (IPS) learning outcomes, it was found that the achievement level was low. Observations showed that, in general, students had not reached the expected mastery learning standard determined by the school-based curriculum (SBC). Of the 20 students, only 10 students (50%) achieved the minimum mastery criterion (KKM) of 65 in social studies. The low learning outcomes were also caused by the lack of variation in teaching methods and the limited use of instructional strategies that could engage students actively, creatively, and joyfully in the learning process. This study was conducted as a classroom action research, which is one of the teacher’s efforts to improve the quality of learning in the classroom. Based on the research data, students’ IPS learning outcomes showed a significant improvement from the preliminary data through the first and second cycles. The percentage of students achieving mastery increased from 50% in the preliminary data to 70% in the first cycle, and further increased to 80% in the second cycle among the 20 sixth-grade students of SD Negeri 007 Kampung Baru.